Parental Job Loss and Children's Careers - Kristiina Huttunen; Krista Riukula (Institute of Labor Economics (IZA), 2019)
We study the effect of parental job loss on children's outcomes using administrative data from Finland. We focus on two channels through which parental job loss can affect children's careers: 1) by affecting the child's field of study choices and 2) by weakening social ties to the labor market. We find evidence supporting both mechanisms: a father's job loss decreases the likelihood of the child choosing the father's field of study or finding employment in the father's plant. Children of displaced fathers have lower earnings; however, we find no effects on the outcomes measured before the study choices are made.
Keywords: I24; J24; J63; 330; education; social ties; study field; childhood income; job loss; earnings